2020
DOI: 10.21273/hortsci14940-20
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Visual Quality, and Morphological Responses of 12 Viburnum Taxa to Saline Water Irrigation

Abstract: Viburnums are widely used in gardens and landscapes throughout the United States. Although salinity tolerance varies among plant species, research-based information is limited on the relative salt tolerance of viburnum species. The morphological and growth responses of 12 viburnum taxa to saline solution irrigation were evaluated under greenhouse conditions. Viburnum taxa included Viburnum ×burkwoodii, V. cassinoides ‘SMNV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 19 publications
(41 reference statements)
1
14
0
Order By: Relevance
“…The duration of salinity stress imposed on plants also affects the g S . In this study, all viburnum taxa at the first harvest had a greater g S than those at the second harvest (P = 0.0003) (Table 2), which might result from accumulated salt levels in the substrate (Sun et al, 2020). Liu et al (2017) found that the g S of Forsythia •intermedia 'Mindor' (border forsythia) did not change when irrigated with a saline solution of 5.0 dS • m -1 for 6 weeks, but did decline after 9 weeks of irrigation with the same source.…”
Section: Gas Exchangementioning
confidence: 58%
See 4 more Smart Citations
“…The duration of salinity stress imposed on plants also affects the g S . In this study, all viburnum taxa at the first harvest had a greater g S than those at the second harvest (P = 0.0003) (Table 2), which might result from accumulated salt levels in the substrate (Sun et al, 2020). Liu et al (2017) found that the g S of Forsythia •intermedia 'Mindor' (border forsythia) did not change when irrigated with a saline solution of 5.0 dS • m -1 for 6 weeks, but did decline after 9 weeks of irrigation with the same source.…”
Section: Gas Exchangementioning
confidence: 58%
“…Similar to g S , the E of all viburnum taxa observed in our study decreased at the second harvest compared with the first harvest (P = 0.02) ( Table 3). The increased (cumulative) salinity levels in the substrate might have led to the decreased E observed for viburnum taxa in our study (Sun et al, 2020). At the first harvest, all viburnum taxa irrigated with a saline solution of 5.0 dS • m -1 had a WUE similar to the control except for V. •rhytidophylloides 'Redell' and V. trilobum (Table 4).…”
Section: Gas Exchangementioning
confidence: 74%
See 3 more Smart Citations